ANALISIS FRAMING PEMBERITAAN MEDIA ONLINE MEDIAINDONESIA.COM DAN TVONENEWS.COM TENTANG PENGESAHAN RANCANGAN UNDANG-UNDANG CIPTA KERJA (PERIODE BERITA BULAN MARET-MEI 2023) - Monica Puspitaningrum, Veronica; Riyanto, Buddy; Maserona, Lukas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The approval of the Creation of Work Act, which was implemented on March 21, 2023 by the DPR RI, has reaped many pro-contracts in the middle of society. This issue is not out of the media highlight. Including Mediaindonesia.com and Tvonenews.com who also massively report the issue. The ownership of the two media is under the auspices of government figures. As well as the framing differences presented by the two media, the reason for the researchers to choose both media as the object of research. In this research, use qualitative descriptive methods with data collection techniques through documentation. Then analyzed using the framing theory of Zhongdang Pan & Gerlad M. Kosicki with his four instruments: syntax, script, thematic, and rhetoric. The results of this research show that Mediaindonesia.com frames the issue of the validation of the Creation of Work Act is the right thing, with all it’s usefulness. While Tvonenews.com frames the issue of the validation of the Labour Creation Act is a bad thing and opposed by the workers and society. Keywords: Framing Analysis, Mediaindonesia.com, Tvonenews.com, The approval of the Creation of Work Act